Institutional Racism and Black Resistance as Portrayed through Images and Narratives in American Graphic Novels - Titien Diah Soelistyarini; Nuril Rinahayu; Ridha Dinauri Nuswantari (Universitas Airlangga, 2020)
For centuries, racial discrimination and injustice have resulted in the struggle of African Americans to resist racial inequality. Nevertheless, their struggle has never been easy since racism against African Americans has long been institutionalized. In other words, any kinds of white oppression that marginalized, discriminated, and alienated African Americans have embedded in formal institutions, such as legal, educational, as well as social and political institutions. Accordingly, this study dealt with institutional racism and black resistance in the United States as portrayed through images and narratives in two American graphic novels, Octavia E. Butler’s Kindred: A Graphic Novel Adaptation and John Lewis’ March: Book Three, which depicted different ways African Americans were oppressed by and resisted against institutionalized racism. This study applied African American criticism to reveal the racism and black resistance portrayed in both graphic novels based on Feagin’s and Better’s theories of systemic racism and institutional racism. As this study focused on graphic novels, the analysis combined both narrative and non-narrative elements in making meaning through cues provided in the graphic novels, including stressed words and facial expressions. This study reveals that the whites have successfully oppressed African Americans for so long due to the white racial frame and its embedded racist ideology that enforced segregation system. Furthermore, the findings suggest that only by empowering themselves, African Americans are able to resist institutionalized racism in order to gain their freedom and equality of rights.